EVALUASI PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (LB3) DI RSUD Dr. SOEDRIMAN KABUPATEN SEMARANG - Elisa Maharani; Tri Joko; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
Regional General Hospital Dr. Soedirman Kebumen is one of the Government’s assests that provide health services in Kebumen Regency area. A wide range of health services provided have an impact on the high hospital waste is generated. One of the hospital waste is hazardous materials and toxic waste (LB3). Hazardous materials and toxic waste (LB3) that are not managed properly will cause the impact of environmental pollution, work accident as well as the transmission of the disease. The purpose of this research was to evaluate the management of hazardous materials and toxic waste on sorting, storage, and transport based on the regulation of the Minister of Environment and Foresty Number 56 Year 2015 of Ordinances and Technical Requirements of Waste Management Hazardous Materials and Toxic from Healthcare Facilities. The method of this research is descriptive research with cross sectional approach using kualitatif analysis. The object of this research is the management of hazardous materials and toxic waste (LB3) stage of sorting, storage, and transport. The results showed that most of management of hazardous materials and toxic waste (LB3) were in accordance with the standards eztablished. The requirements have not been met on the stage of sorting, storage and transport is not yet the presence of labeling and symbol on the pastic bag waste, waste pharmaceutical and chemical wastes are categorized using the pastic bag brown, storage of waste that is stored for more than 2 days in a polling station, a temporay storage area that does not yet have an alaarm alerting and first aid facilities, still found the presence of compaction or emphasis on waste using feet, and negligence of the officers against the use of protective tools myself in the process of transporting the waste.